2020
DOI: 10.1109/access.2020.3020099
|View full text |Cite
|
Sign up to set email alerts
|

A CRNN System for Sound Event Detection Based on Gastrointestinal Sound Dataset Collected by Wearable Auscultation Devices

Abstract: In this paper, we set up a novel audio dataset named Gastrointestinal (GI) Sound Set which includes 6 kinds of body sounds Bowel sound, Speech, Snore, Cough, Groan, and Rub. We do sound event detection (SED) based on it, and can accurately detect 6 types of sound events. First, the GI Sound Set is collected by wearable auscultation devices. To ensure generalization, patients from five different hospital departments are recruited for data collection, along with a group of healthy subjects. GI Sound Set refers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…The studies between 1967 and 2022 on this data set have been summarized in Table 1 [ 21 , 22 , 28 , 42 , 61 , 65 , 83 , 87 , 88 , 89 , 91 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ].…”
Section: Auscultation and Recording Technologiesmentioning
confidence: 99%
“…The studies between 1967 and 2022 on this data set have been summarized in Table 1 [ 21 , 22 , 28 , 42 , 61 , 65 , 83 , 87 , 88 , 89 , 91 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ].…”
Section: Auscultation and Recording Technologiesmentioning
confidence: 99%
“…To capture the temporal information of the signals, we added two GRU layers of 32 units each before the final output sigmoid layer. This approach is based on previous literature on audio tagging [51] and ECG detection problems [52].…”
Section: Crnnmentioning
confidence: 99%
“…Zheng et al [11] demonstrated another CRNN model for Gastrointestinal (GI) sound event detection. Their work employed a gastrointestinal sound dataset that includes 6 different types of body sounds, i.e.…”
Section: A Related Studies For Audio Classificationmentioning
confidence: 99%
“…This demonstrates again that the use of BiLSTM layer architectures can potentially increase classification performance. As the use of bidirectional RNN methods was shown to be advantageous in [11] and [14], the concept has been further explored in our research.…”
Section: B Bidirectional Rnn Architecturesmentioning
confidence: 99%